2019
DOI: 10.3390/biom9110719
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine May Abrogate LPS-Induced Oxidative Stress and Neuroinflammation by Regulating Nrf2/TLR4 in Adult Mouse Brains

Abstract: Herein, we assayed the antioxidant and anti-inflammatory potential of caffeine in a lipopolysaccharide (LPS)-injected mouse model of neurodegeneration and synaptic impairment. For this purpose, LPS was injected for two weeks on an alternate-day basis (250 µg/kg/i.p. for a total of seven doses), while caffeine was injected daily for four weeks (30 mg/kg/i.p/four weeks). According to our findings, there was a significant increase in the level of reactive oxygen species (ROS), as evaluated from the levels of lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 36 publications
1
62
0
Order By: Relevance
“…For instance, neuroinflammation and oxidative stress induced in the mouse brain by LPS was attributed to the downregulation of Nrf2, while for it to be restored, reduced activated NFκB and TNFα via TLR4 pathway was required. [ 49 ] A similar mechanistic scenario was also depicted by Yang's group in the mice liver, where LPS suppressed the Nrf2 expression, resulting in an upregulated NFκB pathway and an augmented release of IL‐1β and IL‐6. [ 50 ]…”
Section: Discussionmentioning
confidence: 60%
“…For instance, neuroinflammation and oxidative stress induced in the mouse brain by LPS was attributed to the downregulation of Nrf2, while for it to be restored, reduced activated NFκB and TNFα via TLR4 pathway was required. [ 49 ] A similar mechanistic scenario was also depicted by Yang's group in the mice liver, where LPS suppressed the Nrf2 expression, resulting in an upregulated NFκB pathway and an augmented release of IL‐1β and IL‐6. [ 50 ]…”
Section: Discussionmentioning
confidence: 60%
“…Previous research studies extensively highlighted inflammation as a crucial player in cardiovascular disease [43] and neurodegenerative conditions [6,44], specifically AD [17] and PD [45]. Here, we found that the chronic oral administration of ALA may inhibit Aβ-induced neuroinflammation by regulating the levels of activated TLR4 and its downstream targets, such as GFAP and Iba-1.…”
Section: Discussionmentioning
confidence: 64%
“…After behavioral analyses, the mice were anesthetized via a combination of ketamine and xylazine and euthanized, as previously described [6,38]. The brain parts were separated and homogenized in PRO-PREP TM extraction solution (iNtRON Biotechnology, Inc., Sungnam, South Korea) and centrifuged (13,000 RPM for 25 min at 4 • C).…”
Section: Immunoblotingmentioning
confidence: 99%
See 1 more Smart Citation
“…While this is clearly significant, it remains speculative until detailed studies with pure enzyme are carried out. Nonetheless, it is known that these compounds have a wide variety of health benefits when present in the diet, especially on neurodegenerative disease [4,5,60,61] and must, therefore, reach levels sufficient to exert pharmacological action. The true levels of methylxanthine interacting with the enzyme under the conditions of this study were impossible to estimate due to the possibility of interaction with lipids and tissue components.…”
Section: Discussionmentioning
confidence: 99%